2019
DOI: 10.1097/ico.0000000000002050
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparity in How Pain Sensitivity Influences Dry Eye Symptoms

Abstract: Purpose: Women have a higher dry eye disease prevalence compared with men, although only relatively minor differences in the ocular surface have been observed. Interestingly, a sex difference in pain sensitivity is known, and recent research suggests that pain sensitivity is associated with dry eye symptoms. This study attempts to discern whether the association between pain sensitivity and dry eye symptoms varies between women and men. Methods: In this prospective cross-sectional study, subjects were seen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“… 2021 ). Supporting findings arise from the recent study by Li and Lin ( 2019 ), where increased DE symptoms of women were associated with a greater pain sensitivity, whereas in men, there was no such association. In the future, studies on sex differences in self‐reported symptoms and potential differences in corneal sensitivity might help to understand better these findings.…”
Section: Discussionsupporting
confidence: 52%
“… 2021 ). Supporting findings arise from the recent study by Li and Lin ( 2019 ), where increased DE symptoms of women were associated with a greater pain sensitivity, whereas in men, there was no such association. In the future, studies on sex differences in self‐reported symptoms and potential differences in corneal sensitivity might help to understand better these findings.…”
Section: Discussionsupporting
confidence: 52%
“…There were significantly more females than males in the group that exhibited OSC. This difference may be due to higher dry eye prevalence in females than males 29 36 . Sex-associated differences have been noted in the amount of meibomian lipids on the lid margins, greater in males than in females, and in lacrimal gland physiology 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Li and others tried to find a connection between DED symptoms and sensitivity to pain for both sexes. In women, greater pain sensitivity was found to be associated with higher OSDI and other DED questionnaire scores, whereas in men, depending on the questionnaire, greater pain sensitivity was either not associated with dry eye symptoms or associated with decreased dry eye symptoms [ 36 ]. In our study, OSDI scores increased postoperatively in women, although objective test results, such as Schirmer’s test and TBUT did not change significantly.…”
Section: Discussionmentioning
confidence: 99%